2018
DOI: 10.1002/cctc.201701783
|View full text |Cite
|
Sign up to set email alerts
|

Solid Molecular Frustrated Lewis Pairs in a Polyamine Organic Framework for the Catalytic Metal‐free Hydrogenation of Alkenes

Abstract: We report for the first time a metal‐free heterogeneously catalyzed hydrogenation using a semi‐solid frustrated Lewis pair (FLP). The catalyst consists of a solid polyamine organic framework and molecular tris(pentafluorophenyl)borane (BCF) that form a semi‐immobilized FLP in situ in the catalytic hydrogenation of diethyl benzylidenemalonate. 11B NMR spectroscopy proves the successful hydrogen activation by the FLP. Furthermore, the B−N interactions between the polyamine and BCF are investigated by IR and soli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 47 publications
(65 reference statements)
0
19
0
2
Order By: Relevance
“…[83] Fori nstance,f ree-radical polymerization of vinyl-functionalized diphosphines generated crosslinked polymeric networks (42,F igure 9, top) that, upon ligation with Rh, promoted the highly regioselective hydroformylation of styrene and long-chain olefins with better activity and selectivity than homogeneous analogues. [85] In an elegant recent study Ragogna et al showed that phosphane-ene reactions offer an alternative approach to Pcontaining polymer networks.R elated to thiol-ene "click" chemistries, [87] phosphane-ene reactions have the potential to efficiently decorate polymers with desirable phosphine functionalities.R agognasg roup used alkyl linkers with two primary phosphines, ( 44), to rapidly generate P-based polymer networks via phosphane-ene coupling (45 and 46, Figure 10). [85] In an elegant recent study Ragogna et al showed that phosphane-ene reactions offer an alternative approach to Pcontaining polymer networks.R elated to thiol-ene "click" chemistries, [87] phosphane-ene reactions have the potential to efficiently decorate polymers with desirable phosphine functionalities.R agognasg roup used alkyl linkers with two primary phosphines, ( 44), to rapidly generate P-based polymer networks via phosphane-ene coupling (45 and 46, Figure 10).…”
Section: Lewis Bases For Metal Coordination and Catalysismentioning
confidence: 99%
See 2 more Smart Citations
“…[83] Fori nstance,f ree-radical polymerization of vinyl-functionalized diphosphines generated crosslinked polymeric networks (42,F igure 9, top) that, upon ligation with Rh, promoted the highly regioselective hydroformylation of styrene and long-chain olefins with better activity and selectivity than homogeneous analogues. [85] In an elegant recent study Ragogna et al showed that phosphane-ene reactions offer an alternative approach to Pcontaining polymer networks.R elated to thiol-ene "click" chemistries, [87] phosphane-ene reactions have the potential to efficiently decorate polymers with desirable phosphine functionalities.R agognasg roup used alkyl linkers with two primary phosphines, ( 44), to rapidly generate P-based polymer networks via phosphane-ene coupling (45 and 46, Figure 10). [85] In an elegant recent study Ragogna et al showed that phosphane-ene reactions offer an alternative approach to Pcontaining polymer networks.R elated to thiol-ene "click" chemistries, [87] phosphane-ene reactions have the potential to efficiently decorate polymers with desirable phosphine functionalities.R agognasg roup used alkyl linkers with two primary phosphines, ( 44), to rapidly generate P-based polymer networks via phosphane-ene coupling (45 and 46, Figure 10).…”
Section: Lewis Bases For Metal Coordination and Catalysismentioning
confidence: 99%
“…[84] When embedding sterically hindered Lewis basic functional groups,h eterogeneous FLP systems can be generated by addition of organoborane Lewis acids.T he first such polymer-supported FLPs were reported by Thomas et al [86] They prepared crosslinked porous materials with tunable steric hindrance at Pv ia Yamamoto coupling of bromosubstituted triarylphosphines.I nt he presence of B(C 6 F 5 ) 3 , aheterogeneous FLP system is generated in situ, resulting in splitting of dihydrogen at room temperature.I narelated study,the semi-immobilized polyamine network 43 was mixed with B(C 6 F 5 ) 3 and employed in the hydrogenation of diethyl benzylidenemalonate,showing superior activity over amolecular FLP system under homogeneous conditions (Figure 9, bottom). [85] In an elegant recent study Ragogna et al showed that phosphane-ene reactions offer an alternative approach to Pcontaining polymer networks.R elated to thiol-ene "click" chemistries, [87] phosphane-ene reactions have the potential to efficiently decorate polymers with desirable phosphine functionalities.R agognasg roup used alkyl linkers with two primary phosphines, ( 44), to rapidly generate P-based polymer networks via phosphane-ene coupling (45 and 46, Figure 10). Ther esulting polymer networks exhibit the capacity of sequestering O 2 ,a ni mportant capability for the…”
Section: Lewis Bases For Metal Coordination and Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…[84] Wenn sterisch anspruchsvolle,L ewis-basische,f unktionelle Gruppen eingebettet werden, kçnnen durch Zugabe von Organoboran-Lewis-Säuren heterogene FLP-Systeme erzeugt werden. [85] In einer eleganten, aktuellen Studie zeigten Ragogna et al,d ass Phosphan-En-Reaktionen einen alternativen Zugang zu P-haltigen Polymernetzwerken bieten. [86] Sie synthetisierten vernetzte porçse Materialien mit abstimmbarer sterischer Hinderung an P über eine Yamamoto-Kupplung von Bromsubstituierten Tr iarylphosphanen.…”
Section: Angewandte Chemieunclassified
“…Es zeigt eine überlegene Aktivitätg egenüber derjenigen eines molekularen FLP-Systems unter homogenen Bedingungen (Abbildung 9, unten). [85] In einer eleganten, aktuellen Studie zeigten Ragogna et al,d ass Phosphan-En-Reaktionen einen alternativen Zugang zu P-haltigen Polymernetzwerken bieten. ¾hnlich zur Thiol-En-"Klick"-Chemie [87] haben Phosphan-En-Reaktionen das Potenzial, Polymere effizient mit gewünschten Phosphan-Funktionen auszustatten.…”
Section: Angewandte Chemieunclassified